2006
DOI: 10.1002/jsfa.2546
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant content and ascorbate metabolism in cherry tomato exocarp in relation to temperature and solar radiation

Abstract: Considering the economic importance of the tomato and its nutritional benefits to human health, a study was made of how two different environmental factors (temperature and overall solar radiation) influence the nutritional quality of cherry tomatoes during the plant full production cycle. Solanum lycopersicum L. cv. Naomi plants were grown in an experimental greenhouse. Three fruit samples were taken over the full production period: first sampling at the beginning of harvest (7 January 2004), second at mid-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 39 publications
11
92
1
5
Order By: Relevance
“…A clear symptom of oxidative damage is cell membrane degradation; therefore, MDA -a product of membrane lipid peroxidation -is an excellent marker of oxidative stress (Del Rio et al, 1996). In this study a significant increase of MDA levels in tomato leaves upon salt and water stress treatments of the plants was obseved, in agreement with previous reports showing a salt-induced increase of MDA contents in tomato leaves (Shalata and Thal, 1998), roots (Shalata et al, 2001) and fruits (Rosales et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…A clear symptom of oxidative damage is cell membrane degradation; therefore, MDA -a product of membrane lipid peroxidation -is an excellent marker of oxidative stress (Del Rio et al, 1996). In this study a significant increase of MDA levels in tomato leaves upon salt and water stress treatments of the plants was obseved, in agreement with previous reports showing a salt-induced increase of MDA contents in tomato leaves (Shalata and Thal, 1998), roots (Shalata et al, 2001) and fruits (Rosales et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…One of the most characteristic phytonutrients in tomato fruit, Lyc represents roughly 80% of all carotenoids and has a high capacity to eliminate ROS (Rao et al, 1998). Many studies have demonstrated a strong relation between the nutritional quality of tomato and its Lyc content (Constán-Aguilar et al, 2014; Rosales et al, 2006). Also, K significantly affects the concentration of such pigments as Lyc and β-carotene, which can be used as inner-quality indicators for tomato, based on analytical and sensorial properties (Ramí rez et al, 2012).…”
Section: Antioxidant Capacity and Phytonutrientsmentioning
confidence: 99%
“…These results appear to agree with those of the present study at 24 and 29 WAT (Table 3) (Figs. 1 A and 2 A, 2B), as the decline in the lycopene content could be due to the oxidation of this compound to β-carotene; however, β-carotene degradation also intensifies from 35 to 40ºC (Rosales et al, 2006;Gautier et al, 2005).…”
Section: Antioxidant Capacity and Phytonutrientsmentioning
confidence: 99%
“…Air temperature reduction is one of the tomato greenhouses main objectives (ROSALES et al, 2006), since elevated temperatures resulted from high light intensity can severely limit productivity and nutritional quality of this crop (ADAMS et al, 2001). To this end, shading screens are the most used option (SERRANO et al, 2001), principally the thermoreflective screens, which have the ability to reduce the sensible heat accumulated inside the greenhouses by the incident solar radiation reflection (GUISELINI et al, 2010).…”
Section: Introductionmentioning
confidence: 99%